P205 Managing the challenges of recruitment of patients with asthma to randomised controlled trials. (2nd December 2011) - Morrison, D; Cameron, E; Braganza, G; Thomson, N C; Chaudhuri, R; Mair, F S
Abstract : Introduction: Many trials do not recruit sufficient participants, particularly from primary care settings, making it difficult to get meaningful results. A recent Cochrane systematic review studying recruitment concluded there is still much to learn. Here we describe details of two MRC funded, primary care based, asthma randomised controlled trials, and their recruitment strategies and challenges. Methods: Trial 1: Examined whether short-term treatment with atorvastatin improves lung function, asthma control and quality of life in smokers with asthma (completed 2009). Trial 2: examined the same question using azithromycin (completed July 2011). The participant flow charts and trial documents of both trials were examined to establish recruitment details. Results: Trial 1: Target to randomise =80, target to complete =68, study extended by 3 months due to slow recruitment. Actual randomised =71, actual completed =60. 54/438 GP practices approached, participated. 2483 patients from practices and 356 from a database of previous trial participants received two mailings via GP surgeries, and then following an ethics amendment via telephone for a small number of surgeries. 331/2483 (11.7%) patients responded positively, and of these 286 were able to be contacted and telephone screened for eligibility, leaving 131 eligible participants. 129/131 attended a screening visit; 58/129 screen failed (eg, due to deterioration in peak flow, unable to wean off regular asthma medications) leaving 71 randomised (2.5%) of total patients invited. Trial 2: similar picture, completed July 2011, extended by 6 months due to slow recruitment. Target to randomise =80, target to complete =68. Actual completed: 71/8398 (<1%) of those invited. Conclusion: Achieving the completion target in randomised controlled trials requires significant administrative support, and the capacity to increase support should difficulties in recruitment be encountered. Closer partnership with primary care practitioners, better access to primary care patient databases and direct contact with potential recruits can overcome this. Loss of potential recruits during the run-in phase needs exploration, and is of significant importance to improve the efficiency of screening to randomisation. Addressing these issues will mean fewer trials are underpowered and hence provide better return for grant awarding bodies.